Language and history : theories and texts - Crowley, Tony (Politics of language., 1996)
In Language in History, Tony Crowley provides the analytical tools for answering such questions. Using a radical re-reading of Saussure and Bahktin, he demonstrates, in four case studies, the ways in which language has been used to construct social and cultural identity in Britain and Ireland. For example, he examines the ways in which language was employed to construct a bourgeois public sphere in 18th Century England, and he reveals how language is still being used in contemporary Ireland to articulate national and political aspirations and why the Irish language died. By bringin.